Predictive relevance of optical coherence tomography indices in conjunction with visual acuity and surgical outcomes of idiopathic macular hole - Sonu Kumar; G Nageswar Rao; Nidhi Sinha; Bhumika Rath; Sabya Sachi Pattanayak; Arttatrana Pal (Heliyon)
Idiopathic macular hole (IMH) is a condition that arises from a combination of interactions among several forces on the fovea, remarkably from vitreous traction in the anteroposterior and tangential directions. Recent studies have highlighted the significance of microincision vitrectomy surgery, and IMH surgery was performed with minimal invasiveness, and visual improvement was an expected outcome. This study aimed to observe the pre-operative optical coherence tomography (OCT) indices correlated with visual acuity in the closure of IMH after surgery. Primarily, the findings were associated with clinical characteristics, including OCT indices, change in best corrected visual acuity (BCVA), clinical factors associated with IMH closure, and prognostic factors for the visual outcomes. This retrospective study included pre- and post-operative BCVA and OCT indices of 110 eyes with IMH. Each OCT variable was subjected to stepwise regression analysis regarding therapeutic factors that predict the need for IMH closure. Our results revealed that the hole form factor (HFF, r = 0.196), macular hole index (MHI, r = 0.669), and tractional hole index (THI, r = 0.085) had a positive correlation with visual acuity. However, basal hole diameter (BHD, r = −0.696) and minimum hole diameter (MHD, r = −0.407) showed a negative correlation. Out of them, HFF, MHI, BHD, and MHD were observed to be statistically significant (p < 0.05). The mean follow-up time was 149 ± 63.22 (85–300) days. The mean baseline BCVA was 0.75 ± 0.44 logMAR (Logarithm of the Minimum Angle of Resolution) units, which was improved to 0.29 ± 0.27 logMAR units at the final follow-up. The surgical success closure rate was 100 % among subjects with IMH. In conclusion, OCT indices were significant indicators of visual success rates in IMH, and OCT measurement could be employed as a single key index in predicting the IMH closure rate. Also, our findings suggested that OCT indices could be utilized as a safe and effective predictor of visual and anatomical outcomes in the case of IMH.